Photodynamic effects of meso-tetra (4-sulfonatophenyl)porphine on human leukemia cells HEL and HL60, human lymphocytes and bone marrow progenitor cells - Grebenová, D; Cajthamlová, H; Holada, K; Marinov, J; Jirsa, M; Hrkal, Z (Journal of photochemistry and photobiology. B, Biology, 1997)
Meso-tetra(4-sulfonatophenyl)porphine (TPPS4), in combination with a light dose of 14 J cm-2, has a profound negative effect on the proliferation and viability of leukemia cells HL60 (human promyelocytic leukemia) and HEL (human erythroleukemia), the viability of normal lymphocytes and the colony-forming activity of human bone marrow progenitor cells. However, normal leukocytes (monocytes, granulocytes) are, to a large extent, resistant to photodynamic treatment (PDT). Whilst DNA fragmentation suggesting apoptosis is induced in HL60 cells, accumulation in the interphase of the cell cycle (G0/G1, G2/M) is mainly operative in the TPPS4-mediated PDT of HEL cells. The "dark" effect of TPPS4 on the cell viability is below 15% up to a concentration of 40 microM.
Keywords: Cell Survival; Photochemistry; Cell Division; leukemie; Humans; Transplantation, Autologous; Lymphocytes; lymfocyty; fotochemie; autologní transplantace; hematopoetické kmenové buňky; lidé; fotochemoterapie; Radiation-Sensitizing Agents; HL-60 Cells; Porphyrins; radiosenzibilizující látky; HL-60 buňky; Photochemotherapy; Bone Marrow Cells; Hematopoietic Stem Cells; porfyriny; Leukemia; viabilita buněk; buňky kostní dřeně; buněčné dělení